Imaging through Nonlinear Metalens Using Second Harmonic Generation. Issue 8 (8th January 2018) - Schlickriede, Christian; Waterman, Naomi; Reineke, Bernhard; Georgi, Philip; Li, Guixin; Zhang, Shuang; Zentgraf, Thomas
Abstract: The abrupt phase change of light at metasurfaces provides high flexibility in wave manipulation without the need for accumulation of propagating phase through dispersive materials. In the linear optical regime, one important application field of metasurfaces is imaging by planar metalenses, which enables device miniaturization and aberration correction compared to conventional optical microlens systems. With the incorporation of nonlinear responses into passive metasurfaces, optical functionalities of metalenses are anticipated to be further enriched, leading to completely new application areas. Here, imaging with nonlinear metalenses that combine the function of an ultrathin planar lens with simultaneous frequency conversion is demonstrated. With such nonlinear metalenses, imaging of objects with near infrared light while the image appears in the second harmonic signal of visible frequency range is experimentally demonstrated. Furthermore, the functionality of these nonlinear metalenses can be modified by switching the handedness of the circularly polarized fundamental wave, leading to either real or virtual nonlinear image formation. Nonlinear metalenses not only enable infrared light imaging through a visible detector but also have the ability to modulate nonlinear optical responses through an ultrathin metasurface device while the fundamental wave remains unaffected, which offers the capability of nonlinear information processing with novel optoelectronic devices. Abstract : A subwavelength plasmonic metalens is realized that works solely in the nonlinear regime by second harmonic generation, while the fundamental near‐infrared wave stays unaffected. Experimental realization of nonlinear imaging verifies real and virtual images formation of real objects at visible wavelengths. This process is not governed by the traditional lens equation but by a modified version of it.